2007
DOI: 10.1007/s00405-007-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen and steroid therapy for idiopathic sudden sensorineural hearing loss

Abstract: In our controlled retrospective analysis of medical records in tertiary care academic medical center, we aimed to investigate the therapeutic effects of hyperbaric oxygen (HBO) therapy combined with steroid administration for idiopathic sudden sensorineural hearing loss (ISSNHL) in comparison with that of steroid administration alone. Our subjects were 130 consecutive inpatients with ISSNHL (hearing levels >/=40 dB; time from the onset of hearing loss to the start of treatment Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 27 publications
2
65
2
Order By: Relevance
“…Combination of HBO and steroid therapy compared to steroid therapy alone significantly improved hearing outcome [25] . The addition of HBO therapy to primaryconventional therapy improved the results when started early after the onset of SSNHL and was more successful in patients with a hearing loss greater than 60 dB [15] . A recent study compared four primary therapy protocols for patients with SSNHL: oral steroid therapy, intratympanic steroid therapy, HBO therapy, and HBO therapy combined with oral steroid therapy [19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of HBO and steroid therapy compared to steroid therapy alone significantly improved hearing outcome [25] . The addition of HBO therapy to primaryconventional therapy improved the results when started early after the onset of SSNHL and was more successful in patients with a hearing loss greater than 60 dB [15] . A recent study compared four primary therapy protocols for patients with SSNHL: oral steroid therapy, intratympanic steroid therapy, HBO therapy, and HBO therapy combined with oral steroid therapy [19] .…”
Section: Discussionmentioning
confidence: 99%
“…[11] It was found that perilymphatic oxygen tension decreased in patients with SSNHL, while under hyperbaric conditions, oxygen tension in the perilymphatic fluid increased by 450% [12,13] . These days, HBO therapy is used as primary or as salvage therapy for sudden haring loss [14][15][16] . However, the results of salvage HBO therapy for SSNHL vary among studies, and its efficacy is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…173,177,235,236,[238][239][240][241] Patients with moderate to severe hearing loss benefit more from HBOT than those with mild hearing loss (moderate hearing loss cutoff was usually at 60 dB). 168,[170][171][172][242][243][244] Results of studies detailing effectiveness of HBOT depend on the choice of outcome measures. 166 fees in academic institutions are approximately $600 to $700 per session, including both technical and professional fees.…”
Section: Supporting Textmentioning
confidence: 99%
“…Although the mechanism of HBO therapy in inner ear has not been still fully understood, today, it is an important adjuvant therapy and being increasingly used in a variety of disorders, such as severe anaemia, decompressive diseases, arterial gas embolism, carbon monoxide poisoning, stimulant of wound healing on refractory wounds, gas gangrene, radiation injury, necrotizing infections, and chronic osteomyelitis [7][8][9]. It has been also used in the management of acute ischemia-related disorders like acute sensorineural hearing loss such as sudden deafness, and acute noise trauma [8,[10][11][12][13][14][15]. But to the best of our knowledge, no study to date have investigated the possible protective effect of HBO against to ototoxic effect of aminoglycoside.…”
Section: Introductionmentioning
confidence: 99%